2022
DOI: 10.3847/2041-8213/aca28e
|View full text |Cite
|
Sign up to set email alerts
|

Directly Tracing Cool Filamentary Accretion over >100 kpc into the Interstellar Medium of a Quasar Host at z = 1

Abstract: We report the discovery of giant (50−100 kpc) [O ii] emitting nebulae with MUSE in the field of TXS 0206−048, a luminous quasar at z = 1.13. “Down-the-barrel” UV spectra of the quasar show absorption at velocities coincident with those of the extended nebulae, enabling new insights into inflows and outflows around the quasar host. One nebula exhibits a filamentary morphology extending over 120 kpc from the halo toward the quasar and intersecting with another nebula surrounding the quasar host with a radius of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 102 publications
1
14
0
Order By: Relevance
“…In addition, turbulence in the CGM can also be produced by Kelvin-Helmholtz instability during the accretion of cool gas streams (e.g., Mandelker et al 2019;Vossberg et al 2019;Li et al 2023), and the motions of fragmented cool gas clumps in disrupted, turbulent mixing zones near the accreting streams are predicted to be subsonic in numerical simulations (e.g., Aung et al 2019). Among our sample, the nebula in the field of TXS0206−048 exhibits compelling signs of cool, filamentary gas accretion from large scales (Johnson et al 2022), suggesting that the observed subsonic turbulence may be in part produced through the accreting streams.…”
Section: Implications For the Multiphase Cgm Dynamicsmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, turbulence in the CGM can also be produced by Kelvin-Helmholtz instability during the accretion of cool gas streams (e.g., Mandelker et al 2019;Vossberg et al 2019;Li et al 2023), and the motions of fragmented cool gas clumps in disrupted, turbulent mixing zones near the accreting streams are predicted to be subsonic in numerical simulations (e.g., Aung et al 2019). Among our sample, the nebula in the field of TXS0206−048 exhibits compelling signs of cool, filamentary gas accretion from large scales (Johnson et al 2022), suggesting that the observed subsonic turbulence may be in part produced through the accreting streams.…”
Section: Implications For the Multiphase Cgm Dynamicsmentioning
confidence: 91%
“…Based on the velocity dispersion of member galaxies in the QSO host group environment, the halo mass of the QSO hosts in our sample is estimated to be ≈10 13 -10 14 M e (see, e.g., Johnson et al 2018Johnson et al , 2022Helton et al 2021;Liu et al 2024). This mass range suggests a viral temperature of T ≈ 10 6 -10 7 K for the underlying hot halo (e.g., Mo et al 2010).…”
Section: Implications For the Multiphase Cgm Dynamicsmentioning
confidence: 96%
“…Detailed analysis of the kinematics and physical properties of the extended gas and galaxies are required to establish whether the [O ] emission originates from gas stripping, outflows or combination of both. Furthermore, there have been detections of extended nebulae (≈ 10 − 120 kpc) in [O ], H 𝛽 and [O ] emission from galaxy groups hosting quasars at 𝑧 ≈ 0.5−1 (Johnson et al 2018(Johnson et al , 2022Helton et al 2021). These observations suggest gas stripping from the interstellar medium of interacting galaxies, and cool, filamentary gas accretion as possible origins of the extended gaseous structures.…”
Section: Comparison With Literature Observationsmentioning
confidence: 99%
“…The metal-enriched halo gas has been more challenging to detect (Rickards Vaught et al 2019), as expected from theoretical grounds due to their lower SB (Bertone & Schaye 2012;Frank et al 2012;Piacitelli et al 2022). This technique has nevertheless seen many recent successes, such as the detection of extended nebulae in [O ] and [O ] emission around quasars (Johnson et al 2018(Johnson et al , 2022Helton et al 2021), galaxy groups and clusters (Epinat et al 2018;Boselli et al 2019;Chen et al 2019), and ultraluminous galaxies (Rupke et al 2019) at 𝑧 < 1. Furthermore, extended Mg emission has been detected around a few galaxies at 𝑧 < 2 using long-slit spectroscopy (Rubin et al 2011;Martin et al 2013) and IFU observations (Rupke et al 2019;Burchett et al 2021;Zabl et al 2021;Shaban et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…During the past ten years, integral field spectrograph (IFS) facilities such as VLT/MUSE [5] and Keck/KCWI [6] have enabled mapping the CGM or even the IGM in emission using several tracers such as Lyα [7][8][9][10][11][12], C IV, He II and C III] [13], and other rest-frame optical emission lines [14,15] out to very large distances from galaxies. Yet Lyα emission can only be observed by ground-based facilities at z ≳ 2, and due to the severe effects of cosmological surface brightness dimming it is very difficult to obtain spatially resolved spectroscopy at such high redshifts.…”
mentioning
confidence: 99%